Analisis Faktor Kesiapan Belajar Peserta Didik Memasuki Jenjang Pendidikan Sekolah Dasar - Novi Ayu Kristiana Dewi; Tri Yuni Hendrowati; Rohmani (CV. Creative Tugu Pena, 2024)
The study analyzes the factors influencing student's learning readiness to enter elementary school. This research is descriptive research with a qualitative approach. The data analysis technique used is the Milles and Hubberman model, starting from data collection and then reducing the data to a more straightforward form so that it can be presented and easy for readers to understand, and the final step is concluding. The data collection methods used were interviews, observation, and literature study. Meanwhile, sample determination was carried out using a specially selected purposive sample. The research results show that age, intelligence, environment, and parental support determine student's learning readiness to enter elementary school.